Performance Evaluation of Hybrid Propulsion System on Fast Patrol Boat - Kyaw, Aung Ye (Maritime Park: Journal of Maritime Technology and Society, 2024)
This paper presents a performance evaluation of a hybrid propulsion system applied to a fast patrol boat. The study aims to analyze the efficiency, fuel consumption, and overall operational effectiveness of the hybrid system compared to conventional propulsion methods. A combination of electric motors and diesel engines is utilized in the hybrid setup, allowing for optimized energy use in varying operational conditions. The performance of the system was evaluated through simulation and sea trials, focusing on key metrics such as speed, endurance, maneuverability, and emission reduction. Results indicate that the hybrid system offers significant advantages in terms of fuel savings and reduced environmental impact, particularly during low-speed or patrol operations. This research provides valuable insights into the practical benefits and challenges of implementing hybrid propulsion systems in maritime security operations.